2022
DOI: 10.1002/jad.12059
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal associations between parent degree/occupation, parent support, and adolescent motivational beliefs in STEM

Abstract: Introduction The United States struggles with racial/ethnic disparities in STEM (science, technology, engineering, mathematics) degrees and occupations. According to situated expectancy‐value theory, the experience and knowledge parents gain through STEM degrees and occupations shape the STEM support they provide and relatedly their adolescents' STEM motivational beliefs. Methods We analyzed data from the High School Longitudinal Study (N = 14,000; 50% female; Mage = 14 years old at 9th grade), which is a rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 71 publications
(113 reference statements)
0
3
0
Order By: Relevance
“…Parents were asked the remaining six items regarding STEM home activities during the past year, for example, “Built or fixed something such as a vehicle or appliance.” These 12 items were averaged to create a scale that ranged from 0 to 1. Similar measures have been used in prior studies using situated expectancy‐value theory and social cognitive career theory as frameworks (Lee & Simpkins, 2021; Simpkins et al, 2015; M. T. Wang & Sheikh‐Khalil, 2014) including indicators that combine youth‐ and parent‐reported measures (e.g., Hsieh & Simpkins, 2022). Incorporating different forms of measurement, including different reporters, can help strengthen formative measures to offer a more complete picture of support (Bradley, 2004).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents were asked the remaining six items regarding STEM home activities during the past year, for example, “Built or fixed something such as a vehicle or appliance.” These 12 items were averaged to create a scale that ranged from 0 to 1. Similar measures have been used in prior studies using situated expectancy‐value theory and social cognitive career theory as frameworks (Lee & Simpkins, 2021; Simpkins et al, 2015; M. T. Wang & Sheikh‐Khalil, 2014) including indicators that combine youth‐ and parent‐reported measures (e.g., Hsieh & Simpkins, 2022). Incorporating different forms of measurement, including different reporters, can help strengthen formative measures to offer a more complete picture of support (Bradley, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, prior research finds that noncollege educated parents are a central, positive influence on their adolescents' academic outcomes (e.g., Bryan & Simmons, 2009; Ramos Carranza & Simpkins, 2021). In fact, some studies suggest that STEM support may have a larger impact on youth with noncollege educated parents when compared to students with college educated parents (Garriott & Nisle, 2018; Hsieh & Simpkins, 2022). These positive processes in families with noncollege educated parents are often ignored or overshadowed by the comparisons between college and noncollege educated parents.…”
Section: Introductionmentioning
confidence: 99%
“…Many career-related decisions have been made in family context [80]; therefore, parents' perceptions and beliefs play a key role in career interests and choices for adolescents [81]. Although a considerable body of research focused on parent factors [25,82,83], less attention has been paid to which parent factors influence adolescents career intentions in math-intensive fields in particular [84]. Recent research [38] revealed that the direction of the actual or perceived parent factors on adolescents' motivational beliefs in particular STEM fields is not clear.…”
Section: The Importance Of Adolescencementioning
confidence: 99%
“…Ebeveyn katılımı çerçevesine göre ebeveyn desteği öğrencilerin akademik başarısı ve motivasyonu için çok önemlidir. Durumlu beklenti-değer kuramına göre, ebeveynlerin meslek eğitimlerini FETEMM alanlarından birinde yapmış olmaları ve mesleklerinde edindikleri deneyim ve bilgi, çocuklarına FETEMM derslerinde verdikleri desteği ve buna bağlı olarak ergenlerin FETEMM derslerine ilişkin motivasyon inançlarını şekillendirmektedir (Hsieh & Simpkins, 2022).…”
Section: Destekunclassified
“…Araştırmalardan elde edilen bulgular, ebeveynlerin fayda değeri inançlarını verdikleri çeşitli destek davranışlarıyla (müze ziyaretleri, ev ödevlerine katılım, cesaretlendirme, ortak etkinlik ve materyal sağlama gibi) çocuklarına aktararak onların FETEMM alanlarındaki motivasyonlarını ve kariyer arayışlarını arttırma konusunda önemli bir rol oynayabileceklerini göstermiştir (Gann & Carpenter, 2019;Hyde vd., 2017;Kang vd., 2018;Simpkins vd., 2012). Son yıllarda yürütülen boylamsal araştırmaların bulguları da bu sonuçlarla benzerlik içermektedir (Dotterer, 2022;Hsieh & Simpkins, 2022). Yine araştırmalara göre, ebeveynler okullarda yeni teknolojilerle yürütülen öğretim uygulamalarını çocukları için faydalı bulmakla birlikte çocuklarını destekleme konusunda kendilerine çok az güvenmektedir (Feng vd., 2011;Lin vd., 2012).…”
Section: Destekunclassified